A Reference Section Through Fast‐Spread Lower Oceanic Crust, Wadi Gideah, Samail Ophiolite (Sultanate of Oman): Trace Element Systematics and REE Crystallization Temperatures—Implications for Hybrid Crustal Accretion. Issue 3 (17th March 2022) - Müller, Samuel; Garbe‐Schönberg, Dieter; Koepke, Jürgen; Hoernle, Kaj
Abstract: Oceanic gabbros are the most abundant rocks close to Earth's surface. Here we present new data from a consistent profile through the paleocrust of the Samail Ophiolite (Oman), which is thought to provide the best analog for modern fast‐spreading oceanic crust. Incompatible trace elements of co‐existing plagioclase and clinopyroxene fractionate from the mineral core to rim and up section from layered to foliated to varitextured gabbros. Layered gabbro parental melts correspond to mid‐ocean‐ridge basalts (MORB), and plagioclase Ca# shows a pronounced inverse zonation. Likely, they crystallized in situ from hydrous melts, compositionally buffered by replenishment at equilibrium to MORB and near steady‐state boundary conditions. Further upsection, the compositional variability increases. Foliated gabbro rim and core compositions indicate increased fractionation and disequilibrium to MORB, triggered by open‐system fractional crystallization within a heterogeneous magma plumbing structure, characterized by magma mixing, varying ambient water activities, and boundary conditions. Varitextured gabbros are chemically diverse with parental melts partially more primitive than MORB, suggesting that primitive melts directly reach the axial melt lens (AML). REE‐in‐plagioclase‐clinopyroxene thermometry compared to and supported by anorthite‐in‐plagioclase thermometry reveals a relationship of T REE An ${T}_{\text{REE}}^{\text{An}}$ [°C] = 6.1 ± 0.2 × An + 706 ± 19. Crystallization temperatures of the layered gabbros cover a narrow range of 1216 ± 14°C. Considerable temperature variability of 1077–1231°C is observed further upsection, featuring a thermal minimum within the foliated gabbros. This minimum is assumed to represent a zone where the fractionated descending crystal mushes originating from the AML meet with evolved liquids expelled from deeper crustal levels. Our findings suggest hybrid accretion of fast‐spread crust. Plain Language Summary: Oceanic crust, the crystalline basement beneath the ocean‐floor sediments is difficult to be sampled by shipboard drilling operations, but can be obducted onto continents by tectonic movement of lithospheric crustal fragments to form ophiolites. These rock formations serve as an analog to in‐situ crust. They can be samples along a profile from extrusive basaltic rocks to gabbros to the upper mantle giving access to the earth's interior. The geochemical and thermal evolution along a profile of paleocrust is crucial for gaining knowledge of the crust's accretional dynamics and formation processes. Our data suggest that the lower part the layered gabbros, are formed by a fundamentally different process than the upper foliated, and varitextured gabbros. While geochemical signatures systematically evolve upsection and the temperature structure is homogeneous for the lower part, the upper part is characterized by much higher dynamics and lower crystallization temperatures. Therefore, the crust forms in a hybrid process, where the lower part is dominated by near steady‐state in situ crystallization in equilibrium with the parental melt. The upper part is formed in a more heterogeneous environment, dominated by subsiding crystal mushes, which mix with more primitive melts under disequilibrium conditions, yielding enhanced chemical variability. Key Points: Geochemical profiles reveal continuous evolution of incompatible elements for the layered, and diverse fractionation for the upper gabbros REE and anorthite thermometry shows a homogenous temperature structure for the lower, and a variable temperature record for the upper crust Both suggests a hybrid model, with lower crust replenished in situ accretion and upper crust melt mixing and variable equilibrium dynamics